Degradation behaviors of perfluorosulfonic acid polymer electrolyte membranes for polymer electrolyte membrane fuel cells under varied acceleration conditions. Issue 3 (18th December 2012) - Mu, Shichun; Xu, Cheng; Yuan, Qing; Gao, Ying; Xu, Feng; Zhao, Pei
Abstract The degradation of perfluorosulfonic acid (PFSA) membranes (e.g., Nafion membranes) in polymer electrolyte membrane fuel cells has caused wide widespread concern. However, their degradation behaviors, which lead to the damage of fuel cells, need to be investigated under alternative accelerating environments by the simulation of fuel‐cell operating conditions. Nafion membranes showed a homogeneous degradation behavior during hydrogen peroxide (H2O2) aging, whereas a nonhomogeneous (or crack‐type) degradation behavior occurs for Nafion membranes aged in an H2O2/Fe2+ system (Fenton's reagent), where plenty of the typical microcracks appeared. Interestingly, in the case of nonhomogeneous degradation, the membrane presented a lower fluoride emission rate than that with the homogeneous degradation; this indicates a possible selective attack model of free radicals to both CF2 and the defect end groups in PFSA membranes. In addition, the effects of the different degradation behaviors on the thermal stability and water uptake of membranes were examined by thermogravimetric analyses. H2 crossover and single‐fuel‐cell tests were carried out to evaluate the influence of the degradation behaviors on the fuel‐cell performance. These showed that the membrane with a nonhomogeneous degradation behavior had a higher hydrogen crossover and was more destructive than that with a homogeneous behavior. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013